Etude de quelques paramètres de la biométrie, de la croissance et de l’histologie d’un Sparidé : le pageot Pagellus acarne (Risso, 1827), pêché dans la baie de Mostaganem. - SOUANE, Assmaa; CHALAKH, Hassiba (My University, 2017)
This initial work helped to bring elements of information on some parameters of biometrics, growth and exploitation of Pagellus acarne captured in the Bay of Mostaganem. The study is based on a set of 150 individuals with a total weight of 18.15 Kg, 126 females and 24 males; Sampled in the Bay of Mostaganem during 3 months, between March and May 2017. The sex ratio shows the dominance of females (84%). The vertebral average is 21,71. The calculated relationships reveal a minimal allometry between total length and fork length and also between height and weight. This means that the total length grows slower than the fork length and that the total weight (Wt) grows less quickly than the size (Lt). The growth parameters of Von Bertalanffy were determined by studying size structures and using FISAT II software (version 1.2.0), a software recommended by FAO. The asymptotic length (L•) of the Pagelllus acarne is 26,78 cm; the growth coefficient (K), which determines the fish's speed to approach the asymptotic length, is high, it is 0,86. The histological study allowed us to study the microscopic anatomy of the target organs (the liver, the gonads (male and female)).
Keywords: Pagellus acarne; baie de Mostaganem; croissance; biométrie; histologie; Mostaganem bay; growth; biometry; histology